2017
DOI: 10.1155/2017/4861570
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy as a Promising Treatment for Prostate Cancer: A Systematic Review

Abstract: Prostate cancer treatment is currently based on surgical removal, radiotherapy, and hormone therapy. In recent years, another therapeutic method has emerged—immunological treatment. Immunotherapy modulates and strengthens one's immune responses against cancer. Neoplastic cells naturally escape from the control of the immune system, and the main goal of immune therapy is to bring the control back. Satisfying outcomes after treatment of advanced melanoma and lung cancer suggest a great potential of immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…The FDA’s approval of ipilimumab (a monoclonal antibody that targets cytotoxic T-lymphocyte-associated protein 4 (CTL-4) in melanoma) and sipuleucel-T (a personalized immunotherapy treatment for prostate cancers) encourages further immunotherapy research in glioma. While the benefit of immunotherapy has been well established in melanoma and prostate cancers [ 14 , 49 ], it is still being evaluated for the treatment of GBM and other astrocytic tumors. For example, a peptide-based vaccine plus poly-ICLC for low-grade gliomas using four targets (IL-13RA2, EphA2 receptor, Wilms tumor 1 and survivin) was well tolerated in patients with grade II glioma [ 50 ].…”
Section: Targeted Therapies For Gliomasmentioning
confidence: 99%
“…The FDA’s approval of ipilimumab (a monoclonal antibody that targets cytotoxic T-lymphocyte-associated protein 4 (CTL-4) in melanoma) and sipuleucel-T (a personalized immunotherapy treatment for prostate cancers) encourages further immunotherapy research in glioma. While the benefit of immunotherapy has been well established in melanoma and prostate cancers [ 14 , 49 ], it is still being evaluated for the treatment of GBM and other astrocytic tumors. For example, a peptide-based vaccine plus poly-ICLC for low-grade gliomas using four targets (IL-13RA2, EphA2 receptor, Wilms tumor 1 and survivin) was well tolerated in patients with grade II glioma [ 50 ].…”
Section: Targeted Therapies For Gliomasmentioning
confidence: 99%
“…In papers [1,2], it has been shown that the rate of increase of the prostate specific antigen (PSA) can be modified in terms of vaccinations that stimulate the patients' immune system. If it is supposed that PSA level can be treated as marker for disease load in PC, then one can build a model that describes mathematically appropriately adjusted immunotherapy to treat PC [2,3]. Using such a model, one can shown that the efficacy of immunotherapy can be improved by changing the interdosing intervals rather than the dose itself [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, prostate cancer is one of the most common causes of cancer death in the male population [ 1 , 2 ]. In recent years, surgical prostatectomy, radiotherapy, hormone therapy, and immunotherapy have been the major methods used to treat prostate cancer, but treatment options remain limited in advanced-stage disease [ 3 7 ]. High rates of metastasis and cancer-associated mortality worsen the prognoses of prostate cancer patients, especially for patients with advanced-stage prostate cancer [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%